Associations between bioaerosols, lung function work-shift changes and inflammatory markers: A study of recycling workers - Karoline Kærgaard Hansen; Vivi Schlünssen; Karin Broberg; Kirsten Østergaard; Margit W Frederiksen; Torben Sigsgaard; Anne Mette Madsen; Henrik Albert Kolstad (Nordic Association of Occupational Safety and Health (NOROSH), 2024)
OBJECTIVES: We investigated associations between bioaerosol exposures and work-shift changes in lung function and inflammatory markers among recycling workers. METHODS: Inhalable dust was measured with personal samplers and analyzed for endotoxin, bacteria, and fungi (incubated at 25 °C and 37 °C) levels. Lung function (FEV1, FVC) was measured before and after work-shifts and serum concentrations of inflammatory markers (CRP, SAA, CC16, IL1B, IL2, IL4, IL5, IL6, IL8, IL10, IL13, and TNF) after the shift. Associations were explored by linear mixed-effects models. RESULTS: We included 170 measurements from 88 production workers exposed to inhalable dust, endotoxin, bacteria, and fungi (25 °C and 37 °C) at geometric mean levels of 0.6 mg/m3, 10.7 EU/m3, 1.6×104 CFU/m3, 4.4×104 CFU/m3, and 103 CFU/m3, respectively, and 14 administrative workers exposed at 7-fold lower levels. No associations were observed between bioaerosol exposures and work-shift change in lung function. IL2, IL6, IL10, and TNF concentrations were positively associated with inhalable dust levels, SAA and IL6 with bacteria, CRP, SAA, IL8, and TNF with fungi (25 °C or 37 °C), with the latter being the only statistically significant finding (exp(β) 1.40, 95% confidence interval 1.01-1.96). CONCLUSIONS: This study of recycling workers exposed to bioaerosol levels generally below those of farmers and compost workers and above background levels did not indicate any acute effect on lung function. Several inflammatory markers tended to increase with exposure, suggesting a systemic effect. Future research should combine data from bioaerosol-exposed workers to uncover health risks that may form the basis for health-based occupational exposure limits.